What Do You Do If You’ve Been at the Poker Table for Twenty Minutes and Still Can’t Spot the Sucker? Implications for Individual Investors - Samsa, Greg (Archives of Business Research, 2018)
In comparison with other market participants, individual investors face an informational deficit. Recognizing this, we ask whether strategies exist which might nevertheless hold out hope for them outperforming the market. We proceed by simulating the behavior of mean-regressing stocks, and estimate the excess returns of a strategy of writing a short-term covered call option and, if the option is not exercised, selling the stock the next time it exceeds the purchase price. Excess returns in the range of 4-6% were observed. Obtaining these returns did not require accepting additional risk, either in the economic or statistical sense, as mean-reverting stocks tend to have both less business risk and lower price volatility than others. Nor did they require that the investors purchase stocks below their true value, only that the investor could identify mean-reverting stocks, and also identify a lower bound on the value around which prices will regress. One of the advantages possessed by individual investors is that their trading behavior is unlikely to affect prices, and thus more strategies are realistically available to them. This is an example of a strategy which couldn’t be easily implemented by an institution but might be appropriate for an individual investor.